Knowledge management as a factor for the formulation and implementation of organization strategy - Rony Dayan; Peter Heising; Matos, F. (Journal of Knowledge Management, 2017)
Purpose: Knowledge management (KM) and organization strategy are both important to the success of an organization. This study aims to assess the research needs of their interrelationship. Design/methodology/approach: The research is based on a collection of over 200 interviews of KM worldwide experts. Their inputs have been categorized based on the frequency of their occurrence. Findings: This study looked at the research themes recommended by the experts and concluded that KM is to be regarded as a factor for the formulation and implementation of the organization strategy. Research limitations/implications: The sample of scholars and practitioners interviewed, the analysis approach used and the use of broad questions and dimensions are some of the limitations of this study. Nevertheless, a variety of effects KM has on the formulation and implementation of company strategy has emerged. Practical implications: Organizations would improve their chances of success in a changing and competitive world by integrating the KM approach, methods and goals within the articulation of their strategy. Originality/value: This study is original in variety because of the wide demographic sample supplied, and to its involvement both of KM academic experts as well as of practitioners. Its value is in the recommendations on the research of KM and organization strategy that would be of value, not only to organizations looking for ways to make their strategy more effective but also to those willing to implement KM in a better way.